Dampak suku bunga the fed dan harga minyak dunia terhadap pergerakan cryptocurrency - Elma Anjelina Sondakh; Gatot Iwan Kurniawan; Susinah Kuntadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Cryptocurrency is the newest type of asset allowed by the Commodity Futures Trading Regulatory Agency (Bappebti) to invest in Indonesia. Cryptocurrency is unique in its transactions because it has no underlying assets and is decentralized. So that cryptocurrency transactions cannot be analyzed with certainty to find valuable information to predict the return of volatility in the bitcoin market such as stocks. The advantage of investing in cryptocurrencies is that an investor will get a very large return, but unfortunately, it can also cause big losses. This study aims to determine the impact of economic indicators, namely the Fed's interest rate and WTI oil prices on bitcoin cryptocurrency. The results of our tests show that the Fed's interest rate has no effect and is not significant on Bitcoin. Meanwhile, WTI crude oil has a significant impact on bitcoin. So it is hoped that the test results can be used as an additional analytical variable in making decisions to invest in cryptocurrency assets.